An Inferential Articulation of Metaphorical Assertions - Kwesi, Richmond (Rivista Italiana di Filosofia del Linguaggio, 2019)
This paper argues for the view that metaphors are assertions by locating metaphor within our social discursive practices of asserting and inferring. The literal and the metaphorical differ not in the stating of facts nor in the representation of states of affairs but in the kind of inferential involvements they have and the normative score-keeping practices within which the inferential connections are articulated. This inferentialist based account of metaphor is supplemented by insights from accommodation theory. The account is significant for our understanding of both metaphor’s figurativeness and cognitive content.